2015
DOI: 10.1155/2015/525369
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-Dependent Changes in Androgen Receptor Expression in the Developing Mouse Cortex and Hippocampus

Abstract: During the perinatal period, male mice are exposed to higher levels of testosterone (T) than females, which promotes sexual dimorphism in their brain structures and behaviors. In addition to acting via estrogen receptors after being locally converted into estradiol by aromatase, T also acts directly through androgen receptor (AR) in the brain. Therefore, we hypothesized that AR expression in the developing mouse cortex and hippocampus was sexually dimorphic. To test our hypothesis, we measured and determined A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 62 publications
3
24
0
Order By: Relevance
“…Decreased expression of Cyp19a1 might prohibit local estrogen biosynthesis in the juvenile mouse cortex/hippocampus and then dampen estrogen responsiveness by reducing transactivation of ERα and/or ERβ by ligands. On the other hand, in agreement with our previous findings (Tsai et al, 2015), Ar mRNA levels drastically increase with age during the first three weeks after birth (Figure 7), which could enhance the responsiveness of the juvenile cortex/hippocampus to androgens through augmented Ar expression. In addition, it has been reported that AR overexpression could also inhibit estradiol‐stimulated ER target gene transcription by competing for transcriptional coregulators (Lanzino et al, 2005) or binding to EREs in breast cancer cells (Peters et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Decreased expression of Cyp19a1 might prohibit local estrogen biosynthesis in the juvenile mouse cortex/hippocampus and then dampen estrogen responsiveness by reducing transactivation of ERα and/or ERβ by ligands. On the other hand, in agreement with our previous findings (Tsai et al, 2015), Ar mRNA levels drastically increase with age during the first three weeks after birth (Figure 7), which could enhance the responsiveness of the juvenile cortex/hippocampus to androgens through augmented Ar expression. In addition, it has been reported that AR overexpression could also inhibit estradiol‐stimulated ER target gene transcription by competing for transcriptional coregulators (Lanzino et al, 2005) or binding to EREs in breast cancer cells (Peters et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Besides the hippocampus, the cerebral cortex is thicker in mice with testes but not in those with ovaries, irrespective of their sex chromosome complement (XX vs. XY), suggesting an effect of gonadal secretions on sexual differentiation of the cortex (Markham et al, 2003). AR and ERs are abundantly expressed in the developing mouse cortex and hippocampus (Kerr et al, 1995; Mogi et al, 2015; Tsai et al, 2015), and once activated, these receptors may act as transcription factors to modulate gene expression. However, the AR‐ or ER‐specific downstream targets that are relevant to sex differences in these brain regions remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the distribution of androgen and oestrogen receptors across the whole brain, as well as local differences in aromatase (which converts testosterone to oestradiol), may underlie the regional specificity of testosterone‐related actions in the CNS . However, given the variety of neural effects that have been demonstrated for DHEA and testosterone, more research is needed to demonstrate which of the above mechanisms are relevant to human brain development.…”
Section: Potential Mechanisms Of Action Of Dhea and Testosteronementioning
confidence: 99%
“…Therefore, sex differences in the effects of testosterone cannot be exclusively attributed to sex differences in aromatase expression or activity, nor to differences in magnitude of exposure between the sexes. In that context, other factors, such as the effects of the sex chromosome complement (XX or XY genotype) or the density of androgen receptors in males vs females, must be taken into account.…”
Section: Conclusion and Future Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation